Senam Aerobik Efektif Menurunkan Indeks Massa Tubuh (IMT) dan Stres pada Mahasiswi Overweight dan Obesitas - Yuliani, Kartika; Putri, Pratiwi Hariyani; Nuriannisa, Farah; Herdiani, Novera; Nisak, Zulfa Shofawatun; Fatmawati, Yuni (Journal of Islamic Medicine, 2022)
Background:   The Covid-19 pandemic increases the risk of weight gain and stress in young adults, especially female college students. Adequate exercise interventions are needed to prevent the incidence of obesity and its complications.  Objective :   To determine the effectiveness of aerobic dance exercise and walking on body mass index (BMI) and stress in overweight or obese female college students.   Methods :  This study was an experimental pre-posttest design with 28 people sample size divided into 2 groups, namely the intervention group (aerobic exercise) and the control group (walking). The treatment was given for 4 weeks with a frequency of 3 times a week. Results : The results showed a significant decrease in stress scores before and after treatment in the intervention and control groups (p 0.05). The post-test stress scores between the intervention and control groups were also significantly different, which means that aerobic exercise has a better effect on reducing stress than walking. A significant decrease in BMI also occurred before and after treatment in the intervention group from an average of 27.65 (2.39) to 27.34 (2.41), but this did not occur in the control group. Conclusion :   Aerobic exercise is proven to be effective in reducing BMI and stress in overweight or obese female students, while walking is only effective for reducing stress but cannot reduce BMI in overweight or obese female studentsKeywords : Female College Student, Body Mass Index, Stress, Aerobic Dance, Walking